PHYSICOCHEMICAL STUDY OF UNANI PHARMACOPEIAL OINTMENT MARHAM GULABI - Abdullah, *Dr; Kurele, Rajeev; Qasmi, Iqbal Ahmad (International Journal of Ayurveda and Pharma Research, 2017)
In Unani medicine drugs derived from natural sources have been used since its origin in Greece about 2000 years ago. During the past decade there has been an ever increasing demand especially from developed countries for drugs from plant sources. This revival of interest is mainly due to the current widespread belief that Unani Medicine is safe and more dependable than synthetic drugs. The SOPs and standardization, which are essential for reproducing efficacy of any drug, have not yet been to be investigated in this formulation. Marahim (Ointments) are the important formulations of Unani System of Treatments, used as topical applicant for cuts, pains and abrasions etc. Most of the ointments contain mineral and/or plant products that vary from formulation to formulation. In the present paper the works on standardization and quality assurance of an ointment (Marhaam Gulabi) are reported. The parameters that are selected are those that are recommended by National Unani Pharmacopoea Committee. Marham Gulabi is a Brick red, semisolid compound with smell of camphor. Its action is mentioned as Daf-e-Taffun, Mudammil and Musakkin, in Unani literature and the mode of administration is topical (Anonymous, 1983). The parameters that are studied are Loss on drying (3.98%), pH 1% & 10% (6.6&6.4), Total Fatty Matter 68.40% and Passed the test of Rancidity, Thermal Stability and Spread ability Test.The heavy metals with in limit, Aflotoxins and Pesticidal residue are also estimated and reported which are abscent.